18F-fluorodeoxyglucose positron emission tomography combined with computed tomography for the prediction of radioiodine therapy response in patients with metastatic differentiated thyroid cancer - T. M. Geliashvili; A. V. Vazhenin; T. P. Berezovskaya; N. G. Afanasyeva; E. V. Vasilyeva; P. I. Garbuzov; V. V. Krylov (Опухоли головы и шеи)
The study objective was to investigate the role of 18 F-fluorodeoxyglucose (18 F-FDG) positron emission tomography combined with computed tomography (PET-CT) as an indirect determination of the differentiation status of metastases and for the prediction of radioactive iodine (RAI) therapy response in patients with metastatic differentiated thyroid cancer.Materials and methods. The 40 metastatic differentiated thyroid cancer patients were enrolled in the study that underwent both post-therapeutic radioiodine scan and PET-CT at the same period.Results. The study found that 12 (30 %) patients responded to RAI therapy. The remaining 28 (70 %) patients not responded to RAI therapy showed stabilization or progression. The accumulation of radioiodine by metastases positively correlated with the total response rate, while the 18 F-FDG avidity is negative. Significant direct correlation with response rate was observed in the group with only radioiodine uptake. However, this correlation was not observed in the patients with both tracers uptake. The patients with 18 F-FDG-positive metastases showed poor response to RAI therapy, regardless of the degree of radioiodine uptake.Conclusion. The 18 F-FDG uptake by metastases is a predictor of a poor response to RAI therapy, even in the presence of RAI uptake. The use of 18 F-FDG PET-CT in patients with metastatic differentiated thyroid cancer can be recommended at the beginning of RAI therapy to clarify the prognosis and provide a personalized approach to the treatment and observation of the most difficult category of patients.